(untitled) (Bangladesh Journal of Medical Microbiology, 2013)
There is a great need to determine the susceptibility of individual Mycobacterium tuberculosis strains as rapidly as possible because emergence of multidrug-resistant and extensively drug-resistant tuberculosis in developing countries. The study was conducted to evaluate the thin layer agar (TLA) media for rapid detection of resistance of M.tuberculosis to rifampicin (RMP) and isoniazid (INH) in clinical isolates and to determine the sensitivity and time to positivity compared to the proportion method. One hundred clinical isolates of M.tuberculosis were studied. For the TLA method, three compartment Petri plate containing 7H11 agar and 7H11 agar with RMP and INH. Results were compared to the proportion method for RMP and INH. The sensitivity for INH and RMP+INH was 85.7 % and 100%. The use of a TLA plate enables the rapid detection of resistance to the two prime anti-tuberculosis drugs RMP and INH in a median time of 9.60 days. TLA was a rapid method for the detection of resistance of M.tuberculosis in the two drugs studied. This faster method is simple to perform, providing an alternative method when more sophisticated techniques are not available in low-resource settings. DOI: http://dx.doi.org/10.3329/bjmm.v7i1.19313 Bangladesh J Med Microbiol 2013; 07(01): 2-6